Peningkatan Hasil Belajar Siswa Dengan Menggunakan Model Problem Based Learning Pada Mata Pelajaran PAI di Kelas VII UPTD SMPN 2 Kec. Lareh Sago Halaban - Refni Wasnani; Syawaluddin Syawaluddin; Deslita Deslita; Azharul Fuaddi; Ikrar Dinata; Jekis Wardi (Jurnal Pendidikan Tuntas, 2024)
This study was motivated by the low student learning outcomes in PAI subjects in Class VII UPTD SMPN 2 Kec. Lareh Sago Halaban. This can be seen from the formative assessment scores of students who have not completed out of 27 students in class VII only 10 students or 37% have completed while 17 students or 63% have not completed. This is caused by the use of learning models that are less innovative, monotonous and still centered on the teacher. This study aims to improve PAI learning outcomes by using the PBL (Problem Based Learning) model. This type of research is Classroom Action Research (PTK). The research subjects were class VII UPTD SMPN 2 Kec. Lareh Sago Halaban students totaling 27 students. This research was conducted as many as IV cycles where each cycle consisted of (1) planning, (2) implementation (acting), (3) observation (observing), and (4) reflection (reflecting). Data collection techniques were carried out by observation and learning outcomes tests. The results showed that the use of the PBL (Problem Based Learning) model in PAI subjects in class VII UPTD SMPN 2 Kec. Lareh Sago Halaban can improve the completeness of student learning outcomes. In the initial pre-research study, the percentage of completeness of learning outcomes was only 10 people (37%) and 17 people (63%) who did not complete out of 27 students. Then after taking action by using the PBL (Problem Based Learning) model, the learning outcomes in cycle I were 14 people (52%) who were complete and 13 people (48%) who were not complete, in cycle II as many as 20 people (74%) who were complete and 7 people (26%) who were not complete, in cycle III as many as 24 people (89%) who were complete and 3 people (11%) who were not complete, in cycle IV all 27 students (100%) were complete. Thus the application of the PBL (Problem Based Learning) model can improve student learning outcomes in PAI subjects in class VII UPTD SMPN 2 Kec. Lareh Sago Halaban.